-8-3x=2x+13

Simple and best practice solution for -8-3x=2x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-3x=2x+13 equation:


Simplifying
-8 + -3x = 2x + 13

Reorder the terms:
-8 + -3x = 13 + 2x

Solving
-8 + -3x = 13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-8 + -3x + -2x = 13 + 2x + -2x

Combine like terms: -3x + -2x = -5x
-8 + -5x = 13 + 2x + -2x

Combine like terms: 2x + -2x = 0
-8 + -5x = 13 + 0
-8 + -5x = 13

Add '8' to each side of the equation.
-8 + 8 + -5x = 13 + 8

Combine like terms: -8 + 8 = 0
0 + -5x = 13 + 8
-5x = 13 + 8

Combine like terms: 13 + 8 = 21
-5x = 21

Divide each side by '-5'.
x = -4.2

Simplifying
x = -4.2

See similar equations:

| C=8/7(k-26) | | 2x+4=2(4x-3)-3(-8+4x) | | 0.2(x-2)+0.5(x+5)=0 | | x^2/3x-5=0 | | 7(2x-4)=8 | | 5b+7=-23 | | X+45=-5y | | 8+12x=52x+x | | 3+6y=13+6z | | 83-4=8x+23 | | 3x-5=3+8-x | | 1/11y^-4 | | (4+3x)+x=36 | | -7/x+2=-4-3/x-3 | | xy+3x=2 | | 5ab+5c=10b-4ac | | -81=-(x-7)-15 | | 3x-5=(x+1) | | 5y+3-1xy=2x+8y-5 | | -7x+9=-40 | | (4_11/4:19/16).(_155/8)= | | 3x+9=-40 | | 87-2x=43x+22 | | 5(w-3)=w-11 | | P=3n | | 5p=6p+12 | | 62-3x=8x+15 | | 19a-7-17a+23=-14 | | 14=7x+4-5x | | 5x+9=58x-2 | | 5-0.03x=0.2-0.05x | | 2n-11+2n-11+n=18 |

Equations solver categories